Dynamic airspace sectorisation for flight-centric operations. (October 2018) - Gerdes, Ingrid; Temme, Annette; Schultz, Michael
Highlights: Proof of concept for artificial airspace sectorization in comparison to traditional. New concept for using non-convex boundaries for the selected part of the airspace. Scalable and dynamic approach will also cover future urban flight operations. Validation of concept for smooth transitions between subsequent sectorisations. Dynamic airspace structure efficiently contributes to flight-centric traffic management. Abstract: Today's air traffic operations follow the paradigm of 'flow follows structure', which already limits the operational efficiency and punctuality of current air traffic movements. Therefore, we introduce the dynamic airspace sectorisation and consequently change this paradigm to the more appropriate approach of 'structure follows flow'. The dynamic airspace sectorisation allows an efficient allocation of scarce resources considering operational, economic and ecological constraints in both nominal and variable air traffic conditions. Our approach clusters traffic patterns and uses evolutionary algorithms for optimisation of the airspace, focusing on high capacity utilisation through flexible use of airspace, appropriate distribution of task load for air traffic controllers and fast adaptation to changed operational constraints. We thereby offer a solution for handling non-convex airspace boundaries and provide a proof of concept using current operational airspace structures and enabling a flight-centric air traffic management. We are confident that our developed dynamic airspace sectorisation significantly contributes to the challenges of future airspace by providing appropriate structures for future 4D aircraft trajectories taking into account various operational aspects of air traffic such as temporally restricted areas, limited capacities, zones of convective weather or urban air mobility. Dynamic sectorisation is a key enabling technology in the achievement of the ambitious goals of Single European Sky and Flightpath 2050 through a reduction in coordination efforts, efficient resource allocation, reduced aircraft emissions, fewer detours, and minimisation of air traffic delays.